Assembled Morphology of Copper‐Thiourea Coordination‐Mediated Metallo‐Supramolecular Polymers. Issue 8 (22nd January 2023) - Qiu, Xiaoyang; Chen, Senbin; Zhu, Jintao
Abstract: Metallo‐supramolecular polymers represent a powerful platform to construct self‐assembled morphologies. Copper‐thiourea (Cu‐TU) coordination interactions, though have been extensively studied in small molecular system, the role of TU motifs in synthetic polymers using metal–ligand coordination to afford supramolecular aggregation and their morphology are often overlooked. Herein, an amphiphilic random copolymer, poly(oligo(ethylene glycol) ethyl acrylate‐ r ‐acylthiourea) (P(OEGEA‐ r ‐ATU)), bearing pendant TU motifs behaving as the ligand to coordinate Cu, a design characterized by core‐coordinated metallo‐supramolecular polymer is rationally synthesized. Indeed, rod‐like nano‐objects are successfully generated via the self‐assembly and coordination interaction between P(OEGEA‐ r ‐ATU) and Cu. The spatial distribution of TU moieties in polymer chain, along with their Cu chelating capability, featuring the interchain coordination interaction, is tightly related to metallo‐supramolecular polymer organization. The specific Cu‐TU coordination interactions enable the prompted robustness and stability of soft P(OEGEA‐ r ‐ATU), induce the polymer chain configuration, which eventually furnish efficient fabrication of rod‐like nano‐objects via straightforward nanoprecipitation procedure. These structural motifs of copper‐coordinated, rod‐like nano‐objects from such metallo‐supramolecular polymers endow the potential therapeutic properties, such as anti‐inflammatory and antitumor effects. Abstract : An amphiphilic random copolymer, poly(oligo(ethylene glycol) ethyl acrylate‐ r ‐acylthiourea) (P(OEGEA‐ r ‐ATU)), bearing pendant thiourea (TU) motifs behaving as the ligand to coordinate Cu is reported. Such TU‐Cu coordination interactions enable the prompted robustness of soft P(OEGEA‐ r ‐ATU), induce the chain configuration and core‐coordinated metallo‐supramolecular polymer, eventually furnish the formation of rod‐like nano‐objects.